Term Rewriting System R:
[x]
f(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))))

Termination of R to be shown.

`   R`
`     ↳Dependency Pair Analysis`

R contains the following Dependency Pairs:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(b, f(a, f(a, f(a, f(b, x))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(b, f(a, f(a, f(a, f(b, x)))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(a, f(b, x))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(b, x)))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(b, x))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(b, x)

Furthermore, R contains one SCC.

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Narrowing Transformation`

Dependency Pairs:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(b, x))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(b, x)))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(a, f(b, x))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(b, f(a, f(a, f(a, f(b, x))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))))

Rule:

f(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))))
one new Dependency Pair is created:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'')))))))))))))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Narrowing Transformation`

Dependency Pairs:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'')))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(b, x)))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(a, f(b, x))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(b, f(a, f(a, f(a, f(b, x))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(b, x))

Rule:

f(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))
one new Dependency Pair is created:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'')))))))))))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 3`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'')))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(b, x))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(b, x)))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(a, f(b, x))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(b, f(a, f(a, f(a, f(b, x))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'')))))))))))))))

Rule:

f(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(b, f(a, f(a, f(a, f(b, x))))))
one new Dependency Pair is created:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x''))))))))))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 4`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x''))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'')))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(b, x))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(b, x)))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(a, f(b, x))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'')))))))))))))

Rule:

f(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(a, f(b, x))))
one new Dependency Pair is created:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x''))))))))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 5`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x''))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'')))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'')))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(b, x))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(b, x)))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x''))))))))))))

Rule:

f(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(b, x))
no new Dependency Pairs are created.
The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 6`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x''))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'')))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'')))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(b, x)))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x''))))))))))

Rule:

f(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'')))))))))))))))
three new Dependency Pairs are created:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'''))))))))))) -> F(a, f(b, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(b, f(a, f(a, f(a, f(b, x''')))))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(a, f(b, x''')))))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'))))))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x')))))))))))))))))))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 7`
`                 ↳Narrowing Transformation`

Dependency Pairs:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'))))))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x')))))))))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(a, f(b, x''')))))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'''))))))))))) -> F(a, f(b, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(b, f(a, f(a, f(a, f(b, x''')))))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x''))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'')))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(b, x)))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x''))))))))))))

Rule:

f(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))))

On this DP problem, a Narrowing SCC transformation can be performed.
As a result of transforming the rule

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x''))))))))))))
two new Dependency Pairs are created:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'''))))))))))) -> F(a, f(b, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(a, f(b, x'''))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'))))))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'))))))))))))))))))

The transformation is resulting in one new DP problem:

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 8`
`                 ↳Polynomial Ordering`

Dependency Pairs:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'))))))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'))))))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'''))))))))))) -> F(a, f(b, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(a, f(b, x'''))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(a, f(b, x''')))))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'''))))))))))) -> F(a, f(b, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(b, f(a, f(a, f(a, f(b, x''')))))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x''))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'')))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(b, x)))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'))))))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x')))))))))))))))))))))

Rule:

f(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))))

The following dependency pairs can be strictly oriented:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'))))))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'))))))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'''))))))))))) -> F(a, f(b, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(a, f(b, x'''))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'''))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(a, f(b, x''')))))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'''))))))))))) -> F(a, f(b, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(b, f(a, f(a, f(a, f(b, x''')))))))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x'))))))))))))))) -> F(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x')))))))))))))))))))))

Additionally, the following usable rule w.r.t. to the implicit AFS can be oriented:

f(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))))

Used ordering: Polynomial ordering with Polynomial interpretation:
 POL(b) =  0 POL(a) =  1 POL(f(x1, x2)) =  x1 POL(F(x1, x2)) =  x2

resulting in one new DP problem.

`   R`
`     ↳DPs`
`       →DP Problem 1`
`         ↳Nar`
`           →DP Problem 2`
`             ↳Nar`
`             ...`
`               →DP Problem 9`
`                 ↳Remaining Obligation(s)`

The following remains to be proven:
Dependency Pairs:

F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x''))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, f(a, x''))))))))))) -> F(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x'')))))))))))))
F(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> F(a, f(a, f(b, x)))

Rule:

f(a, f(a, f(b, f(a, f(a, f(b, f(a, x))))))) -> f(a, f(b, f(a, f(a, f(b, f(a, f(a, f(a, f(b, x)))))))))

Termination of R could not be shown.
Duration:
0:02 minutes